TIBLE: a web-based, freely accessible resource for small-molecule binding data for mycobacterial species - Malhotra, Sony; Mugumbate, Grace; Blundel, Tom L; Higueruelo, Alicia P (Oxford University Press, 2022)
TIBLE is a web-based resource that provides easy access to data on the minimal inhibitory concentrations for small molecules against several mycobacterial species, as well as the target binding and off-target predictions for Mycobacterium tuberculosis. The current version of the database holds the activity data for more than 19 000 distinct small molecules against 39 mycobacterial species, binding data for 106 Mycobacterium tuberculosis target proteins and predictions for their potential off-targets. The resource integrates disparate public data and methods to provide easy access to the minimum inhibitory concentration and binding data, facilitation of data sharing, and identification of small molecules and targets for development of anti-tuberculosis therapeutics.